Improving Employee Performance of Manufacturing Companies in Cirebon Regency Through Training and Job Placement Factors - Raemadhani Patria Azkhali; Rifqi Ahmad Ar-rafi'i (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to examine and ascertain how employee performance, placement, and training affect manufacturing firms. This study employs quantitative methodologies, gathering data via surveys and interviews. The study's population consisted of 177 respondents who worked for manufacturing companies. The Slovin formula was used to calculate the study's sample, which had a 5% margin of error. So, the respondents obtained 123. The findings demonstrated that these factors significantly affect worker performance. Thus, the study's findings support the significance of these elements in raising overall worker performance. This demonstrates that employee performance in manufacturing organizations is significantly influenced by training and placement.